A nomological network for misophonia in two German samples using the S-Five model for misophonia - Remmert, Nico; Jebens, Antonia; Gruzman, Rebecca; Gregory, Jane; Vitoratou, Silia (Frontiers in Psychology, 2022)
The Selective Sound Sensitivity Syndrome Scale (S-Five) is a contemporary and multidimensional self-report instrument measuring different aspects of misophonia. The five-factor scale consists of 25 items measuring the severity of the misophonic experience. The items capture misophonia in relation to internalising and externalising appraisals, perceived threat, aggressive behavior (outbursts), and adverse impact on individuals’ lives. It is complemented by a trigger checklist (S-Five-T), measuring the emotional nature and intensity of reactions to sensory triggers. In this work, we administered the S-Five in two German samples with a majority of individuals with significant misophonia. The S-Five and the supplementary S-Five-T were both translated into German using a rigorous translation procedure (i.e., TRAPD) and were separately tested in large German community samples. Psychometric analyses included the evaluation of the factor structure, measurement invariance with respect to age and gender, reliability (internal consistency and stability over time), and an extensive examination of the construct validity in a proposed nomological network. The nomological network we explore in this work consists of several constructs including different misophonic manifestations, anger and aggression, disgust propensity, anxiety sensitivity, depression, obsessive-compulsive traits, and functional impairment in different life domains. Results indicate evidence in line with the nomological network as demonstrated by strong correlations between the S-Five dimensions and convergent measures. All S-Five dimensions strongly correlated with overall misophonic symptoms (r ≥ .53). Internalising appraisals were highly associated with insight into excessive or disproportionate reactions to sounds (r ≥ .59), externalising appraisals with anger and irritability (r ≥ .46), threat with trait anxiety and dysregulation facets (r ≥ .62), aggressive behavior (outbursts) with anger and behavioral dysregulation (r ≥ .70), and impact with distress and functional impairment (r ≥ .64). The results demonstrate that the S-Five has a robust five-factor structure and allows to draw reliable and valid conclusions about misophonic experiences in German samples. The proposed nomological network gives an initial but likewise thorough insight into the nature of misophonia and provides a formalized fundament to develop and test further hypotheses about misophonia in a more sophisticated and symptom-oriented way.